The Role of Zakat and Waqf in the Economic Empowerment of the People in the Digital Era - Reza Ronaldo; Abiyajid Bustami; Edy Setiawan; Sumadi Buton (Journal of Islamic Economy, 2024)
Zakat and waqf have an important role in strengthening the ummah's economy and building community welfare. In the digital era, this role is increasingly strategic with the existence of various innovations and digital platforms that facilitate the collection, management, and distribution of zakat and waqf. This research aims to analyze the role of zakat and waqf in empowering the people's economy in Indonesia, especially through the use of digital technology. This research method uses a qualitative approach with data collection techniques in the form of literature studies and secondary data analysis related to zakat and waqf digital platforms in Indonesia. The results show that digital technology enables more efficient, transparent, and accountable distribution of zakat and waqf, as well as expanding the reach of beneficiaries. In addition, digitalization also helps increase public awareness of the importance of zakat and waqf in strengthening the economic independence of the ummah. The use of applications and websites in the collection of zakat and waqf funds shows an increase in community participation, especially the younger generation, in supporting social activities and economic empowerment. The conclusion of this study emphasizes the importance of collaboration between zakat and waqf management institutions, the government, and the technology sector to encourage the development of digital platforms that can increase the effectiveness and impact of zakat and waqf in empowering the people's economy.